Lineage‐specific epitope profiles for HPAI H5 pre‐pandemic vaccine selection and evaluation. Issue 5 (12th August 2017) - Qiu, Xueting; Duvvuri, Venkata R.; Gubbay, Jonathan B.; Webby, Richard J.; Kayali, Ghazi; Bahl, Justin
Abstract : Background: Multiple highly pathogenic avian influenza (HPAI) H5 viruses continue to co‐circulate. This has complicated pandemic preparedness and confounded effective vaccine candidate selection and evaluation. Objectives: In this study, we aimed to predict and map the diversity of CD8+ T‐cell epitopes among H5 hemagglutinin (HA) gene lineages to estimate CD8+ T‐cell immunity in humans induced by vaccine candidates. Methods: A dataset consisting of 1125 H5 HA sequences collected between 1996 and 2017 from avian and humans was assembled for phylogenetic and lineage‐specific epitope analyses. Conserved epitopes were predicted from WHO‐endorsed vaccine candidates and representative clade‐defining strains by pairwise comparison with Immune Epitope Database (IEDB). The distribution of predicted epitopes was mapped to each HPAI H5 lineage. We assume that high similarity and conservancy of predicted epitopes from vaccine candidates among all circulating HPAI H5 lineages is correlated with high immunity. Results: A total of 49 conserved CD8+ T‐cell epitopes were predicted at 28 different amino acid positions of the HA protein. Mapping these epitopes to the phylogenetic tree allowed us to develop epitope profiles, or "fingerprints, " for each HPAI H5 lineage. Vaccine epitope percentage analyses showed some epitope profiles were highly conserved for all H5 isolates and may be valuable for universal vaccine design. However, the positions with low coverage may explain why the vaccine candidates do not always function well. Conclusions: These findings demonstrate that our analytical approach to evaluate conserved CD8+ T‐cell epitope prediction in a phylogenetic framework may provide important insights for computational design of vaccine selection and future epitope‐based design.